Research on Electrochemical Machining of Small Deep Holes with Positive and Negative Pulse Power - Li, Zhaolong; Cao, Bingren (Recent Patents on Mechanical Engineering, 2022)
Background: High-temperature alloys, such as the nickel-based alloy, have become the main materials for core components in the aerospace field because of their high strength and good toughness. Therefore, how to improve the machining accuracy and stability of electrochemical machining (ECM) of small deep holes on nickel-based alloy is an important topic for studies. The instantaneous high-density current during the pulse width of pulse ECM is beneficial to the dissolution of nickel-based alloy. Many experts and scholars have studied pulse ECM of small deep holes. Objective: The purpose of this article is to propose and design a positive and negative pulse (PANP) power supply to study the accuracy and stability of ECM of small deep holes on the nickel-based alloy. Methods: First of all, an H-bridge composed of four MOSFET switches is designed to achieve PANP output in the main circuit of the power supply. Then, this article discusses the influence of the ratio of positive and negative pulses on short circuits, the influence of the ratio of positive and negative pulses on the mass removal rate, and the influence of the electrolyte concentration and pulse width on the mass removal rate. Finally, according to the obtained optimal parameters, the influence of the electrolyte pressure on the average radial overcut of hole depth is analyzed. Results: The experimental results show that the short-circuit frequency is reduced by more than 50% compared with non-negative pulses power supply; the ratio of positive and negative pulses, pulse width, and electrolyte concentration and pressure were optimized by experiments in order to improve the mass removal rate of the workpiece and the average radial overcut of hole depth. Conclusion: The designed PANP power supply can improve the machining accuracy and stability of ECM of small deep holes on the nickel-based alloy.
Keywords: average radial overcut